EFFECTIVENESS OF ANTIBACTERIAL EXTRACT OF KENOP (GOMPHRENA GLOBOSA) FLOWER EXTRACT AGAINST GROWTH OF PROPIONIBACTERIUM ACNES BACTERIA - Elvina Veronica; Sang Ayu Arta Suyantari; Widia Danis Swari; Ni Made Ari Purwaningrum; agung bagus sista satyarsa; i made jawi; Prima S. Sudarsa (Universitas Muhammadiyah Ponorogo, 2020)
Acne is a chronic inflammation of the pilosebaceous tissue caused by the bacterium Propionibacterium acne (P.acnes) which often experiences antibiotic resistance. Research on the benefits of herbal plants in dealing with acne is still needed, one of which is the use of Knobs flowers (Gomphrena globosa) which is easily found and has potential as an antioxidant and antibacterial. This study aims to determine the effectiveness of the extract of the flower knob in inhibiting the growth of P.acnes bacteria. The design of this study was purely experimental with the Kirby-Bauer method using MHA (Mueller Hinton Agar) media. A positive control using clindamycin antibiotics and negative control using aquadest. The treatment group consisted of 25%, 50%, 75%, and 100% knob methanol extract with 3 replications. Data analysis using One Way ANOVA to find out the average difference between treatment groups. Based on the results of the study, it was found that the higher the concentration of the extract, the greater the inhibitory power as long as the extract had not reached saturated concentration (p 0.05). There is a decrease in the inhibition zone diameter at 100% concentration because it is influenced by the diffusion rate of a compound and other factors.